2020
DOI: 10.1016/j.ejrad.2020.109342
|View full text |Cite
|
Sign up to set email alerts
|

Dixon or DWI – Comparing the utility of fat fraction and apparent diffusion coefficient to distinguish between malignant and acute osteoporotic vertebral fractures

Abstract: To compare fat fraction (FF) and apparent diffusion coefficient (ADC) as discriminators distinguishing malignant from acute/subacute osteoporotic vertebral fractures. Method: 1.5 T MRIs of 42 malignant and 27 acute/subacute osteoporotic vertebral fractures (38 patients) were retrospectively reviewed. Two readers independently classified fractures as malignant or osteoporotic based on conventional imaging morphology. Diagnostic reader confidence was rated as confident or not confident. FF was derived from axial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 24 publications
1
6
1
1
Order By: Relevance
“…In this study, as regard the in-phase/opposed-phase (IP/OP) ratio there was a statically significant difference between metastatic and non-metastatic benign lesions ratios (P < 0.001) with a significant decrease in ratio in metastatic lesion compared with a high ratio of nonmetastatic benign lesions. These results were in agreement with the results of the study of Donners and his colleagues who reported that the ratio of fat fraction was significantly lower in malignant vertebral fractures compared to osteoporotic fractures [30].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In this study, as regard the in-phase/opposed-phase (IP/OP) ratio there was a statically significant difference between metastatic and non-metastatic benign lesions ratios (P < 0.001) with a significant decrease in ratio in metastatic lesion compared with a high ratio of nonmetastatic benign lesions. These results were in agreement with the results of the study of Donners and his colleagues who reported that the ratio of fat fraction was significantly lower in malignant vertebral fractures compared to osteoporotic fractures [30].…”
Section: Discussionsupporting
confidence: 93%
“…In the current study, the IP/OP ratio cut-point value was slightly higher than that calculated by the study of Donners and his colleagues as they concluded that the best cutoff value for differentiation between malignant and benign lesion was 11.5 % and this may be due to the use of different formula for calculation of the ratio between the two studies [30].…”
Section: Discussioncontrasting
confidence: 80%
“…Previous studies showed good ADC reproducibility of malignant bone lesions and normal bone with repeatability coefficients below 15% [26][27][28][29]. Two-point Dixon-derived rFFs are commonly employed in musculoskeletal imaging, have shown good correlation with MR spectroscopy [30], excellent inter-observer agreement for bone metastases [31] and mean rFF coefficients of variation below 12% in malignant bone lesions [28]. Nevertheless the suggested ADC and rFF values and their combination as utilised in the CT-guided bone biopsy target selection process need to be verified in a prospective setting.…”
Section: Discussionmentioning
confidence: 98%
“…Compared to the present work, the accuracy in that study was higher for PDFF (94.3% compared to 89.9%), but lower for ADC (80.7% compared to 85.4%). More recently, Donners et al have compared the diagnostic accuracy of ADC and fat fraction derived from a 2-point Dixon sequence for differentiation of osteoporotic and malignant vertebral fractures at calculated cut-off values of ≤ 1040 × 10 -6 mm 2 /s for ADC and ≤ 11.5% for PDFF [22]. Besides the fact that fat fraction showed higher diagnostic accuracy than ADC (87% vs. 76%) for distinguishing benign from malignant vertebral fractures, that study also demonstrated that both ADC and fat fraction were capable of improving the diagnostic accuracy, especially specificity, of two independently evaluating radiologists with different levels of expertise, which is in agreement with our observations in VBMLs reported to be uncertain on routine spine MRI.…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, we assessed ADC and PDFF rather as a stand-alone technique to evaluate different types of VBMLs. A dedicated statistical comparison with the diagnostic accuracy of conventional MRI sequences is beyond the scope of the current study and needs to be addressed in the near future; however, two previous studies have already demonstrated that the additive use of quantitative ADC and fat fraction analyses can improve the diagnostic accuracy of radiologists using clinical routine MRI sequences to differentiate benign and malignant vertebral fractures [ 22 ] as well as vertebral hematopoietic marrow islands and metastases [ 40 ].…”
Section: Discussionmentioning
confidence: 99%